Behavior of Concrete Structures of 5-storey Shopping and Residence Buildings due to Earthquakes using Spectrum Response Analysis - Kusbiantoro, Arief; Kusumawardani, Rini; Taveriyanto, Arie; Agung Hermawan, Indra; Danuaji Syahdani, Raka; Jati Priantoro, Wisnu; Restu Bachtiar, M. Vicky; Ageng, Sultan; Rizaldi Fadillah, Akhmad; Rio Pratama, Anggy (Faculty Of Engineering University 17 August 1945 Semarang, 2024)
The 5-storey building with 20 meters high and is located in Jakarta, a building that functions as a shop and residence. As a high-rise building, earthquake analysis of the building is required to determine the seismic pattern using the response spectrum method. The spectrum response method is used to determine the structural performance and compare static analysis and dynamic analysis based on SNI 1726-2019. Then the results obtained for each frame use a combination of cases (static + seismic), for displacement review, there is the highest drift on the 5th floor of 37.04 mm, and the highest drift value on the 5th floor of 4.57x10-3 mm. The internal force in the sample column obtained the same results in story 1 column C1 and C2 of 59.57 kN at Fx, Fy of 4.72 kN and moment of 5.01 kN-m, through a combination (static + seismic). The value of the sample beam on the 3rd floor has the highest value on B1, the Fx value was 4.73x10-14 kN, Fy was 9.09 kN, and the moment was 13.88 kN-m.